Research on using Six Sigma management to improve bank customer satisfaction - Zhiyi Zhuo (International Journal of Quality Innovation, 2019)
In the banking industry, which aims to serve customers, management level and service level are one of the criteria for measuring the core competitiveness of banks. An important indicator of management and service levels is to ensure customer satisfaction with the bank used. Six Sigma management is customer-centric, based on data and facts, adopting improvement measures for the process, focusing on preventive control, emphasizing borderless cooperation, continuous improvement, and the pursuit of quality and efficiency management mechanisms. In this paper, we empirically analyze the reasons why banks affect customer satisfaction and design the bank's Six Sigma service process based on empirical analysis. Finally, in the "Conclusion and discussion" section, the research suggestions for improving bank customer satisfaction are given.
Keywords: 650; Bank; Six Sigma management; Customer satisfaction; Analysis of variance